Choroidal metastases as the sole initial presentation of metastatic lung cancer: Case report and review of literature - Salah, S; Khader, J; Yousef, Y; Salem, A; Al-Hussaini, M; Al-Asady, R (Nepalese Journal of Ophthalmology, 2012)
Background: Choroidal metastasis as an initial presenting feature of metastatic lung cancer is exceedingly rare. External beam radiotherapy (EBRT) is an effective and widely accepted therapeutic modality. However, data addressing the effectiveness of other treatment strategies is limited. Herein, we present a patient with choroidal metastases secondary to lung cancer and review the relevant literature. Case report: A 25-year-old male presented with deterioration of vision. His evaluation revealed bilateral choroidal metastasis secondary to adenocarcinoma of the lung. Unfortunately, his vision continued to deteriorate despite treatment with EBRT and chemotherapy.Conclusion: Metastatic lung cancer can manifest with choroidal metastasis as an initial presentation.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6559 Nepal J Ophthalmol 2012; 4 (2): 339-342